2014
DOI: 10.1186/1749-8090-9-85
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic plication for a huge thoracic meningocele in a patient with Neurofibromatosis

Abstract: Intrathoracic meningoceles associated with neurofibromatosis type I are rare, and the optimal treatment is still unknown. Herein, we present the case of a 48-year-old Asian female with a huge thoracic meningocele associated with cutaneous neurofibromatosis type I and kyphoscoliosis of the thoracic spine. The large thoracic meningocele was successfully treated through thoracoscopic plication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…The approach of thoracotomy for intrathoracic meningocele removal or ligation is especially useful whenever a wider operative field is needed for complete resection of the cyst and anastomosis of the dura mater [ 3 ]. Although the shunt procedure can be a valuable alternative treatment option in patients with high operative risks [ 4 ], it can be ineffective or delayed control of patient’s symptoms, as in our case and other cases [ 5 ]. Therefore, we carefully recommend that a definitive adequate treatment should primarily be performed through thoracotomic or thoracoscopic approaches for large, symptomatic intrathoracic meningoceles in patients with acceptable surgical risks.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The approach of thoracotomy for intrathoracic meningocele removal or ligation is especially useful whenever a wider operative field is needed for complete resection of the cyst and anastomosis of the dura mater [ 3 ]. Although the shunt procedure can be a valuable alternative treatment option in patients with high operative risks [ 4 ], it can be ineffective or delayed control of patient’s symptoms, as in our case and other cases [ 5 ]. Therefore, we carefully recommend that a definitive adequate treatment should primarily be performed through thoracotomic or thoracoscopic approaches for large, symptomatic intrathoracic meningoceles in patients with acceptable surgical risks.…”
Section: Discussionmentioning
confidence: 94%
“…Also, we made a judgement that repairing with meningocele was enough, since it was thick. Recently, Chen et al [ 5 ] reported the successful thoracoscopic plication for a huge intrathoracic meningocele associated with neurofibromatosis type I and kyphoscoliosis of the thoracic spine. In this case, primary CP shunt procedure performed, but shunt dysfunction was developed at postoperative 9 months later.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, this pathology has been documented only a few times in case reports and primarily in patients with NF1. 1 , 4 , 13 Here, we present a case of a nonsyndromic patient with an anterior cervicothoracic myelomeningocele and scoliosis, requiring surgical intervention due to progressive neurological decline. The patient’s progressive weakness was secondary to tethering of the herniated spinal cord within the meningocele sac.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 12 Chen et al. 4 reported a case of a 48-year-old woman with thoracic meningocele that was initially treated with a thoracoscopic cystoperitoneal shunt. The patient’s clinical history was complicated by shunt failure presenting with a large pleural effusion.…”
Section: Discussionmentioning
confidence: 99%
“…It is unlikely that primary repair alone would be successful in these patients because of the inherent abnormalities in the dura; however, thoracoscopic plication has been successful. 3 A posterolateral extradural approach has some advantages over an open thoracotomy. It does not require chest tube drainage, which can be advantageous as the dural repair may not be completely watertight.…”
Section: Discussionmentioning
confidence: 99%